Formula Optimization and Evaluation of Synconine Ointment as an Anti-Acne - Yumna Mufidah; Haryanti; Arini Syarifah (UM Purwokerto Press, 2026)
Acne is a common skin problem that occurs among teenagers and adults, often caused by bacterial activity on facial skin that becomes blocked due to the accumulation of oil and dirt. Cutibacterium acnes is one of the bacteria that can infect the skin and trigger acne formation. Synconine is an alkaloid compound that has been proven to inhibit the activity of gram-positive bacteria; therefore, it was formulated into an ointment preparation. An important component in ointment formulations is the base, which functions as a carrier to deliver the drug to its site of action and achieve the desired pharmacological effect. This study aimed to optimize the PEG 400 and PEG 4000 bases in synconine ointment formulations. The optimum concentration was determined using the disc diffusion method for antibacterial activity testing, while formula optimization was carried out using Design Expert® software version 13 with the Simplex Lattice Design method. The results showed that the optimum concentration obtained was 1.5%, producing an inhibition zone of 13.26 mm, which falls into the moderate category (10–15 mm). The optimum ointment formula was achieved with a PEG 400 concentration of 30% and PEG 4000 of 60%, with a desirability value of 0.911. In conclusion, synconine compounds demonstrated potential antibacterial activity against Cutibacterium acnes, and formula optimization using the Simplex Lattice Design method with variations of PEG 400 and PEG 4000 significantly influenced viscosity, spreadability, adhesion, and pH responses of the ointment preparation.